The Correlation of Social Media Activity and Engagement of a Health NGO with the Outcome of Fundraising Efforts During the COVID-19 Pandemic (Bangladesh Journal of Medical Science, 2021)
Objective: The COVID-19 pandemic saw the involvement of many health non-governmental organisations (NGO) with volunteering work to help reduce the burden of healthcare workers (HCW). IMAM Response and Relief Team (IMARET) is one which is a chapter under the Islamic Medical Association of Malaysia (IMAM); which is also under the umbrella of the Federations of Islamic Medical Associations (FIMA). IMARET often aids HCWs during natural and manmade disasters to help reduce their burden during challenging times by providing manpower, equipment, and logistical assistance. IMARET utilizes social media (SM) for spreading information on their activities to the public, like the COVID-19 fundraising efforts. The objective of this research is to determine the correlation between their Facebook activities and fundraising outcome.Materials and Methods: This is a cross sectional study of Facebook posts and its engagement with Billplz, an online payment platform focused during the initial COVID-19 fundraising effort.Results and Discussion: During the study period, we report 346 Facebook posts with a median (IQR) of 8.00 (6.00,9.00) posts per day. As many as 4,823 donations, median (IQR) at RM34.50(18.75,86.00) was received per day. RM3425,50 (USD 830.52) (1369.00, 8376.25) was collected per day. ‘Organic Likes’ correlated significantly with the number of donations (r=0.419,p=0.006) and amount received (r=0.355,p=0.021). Both ‘Post Reach’ and ‘Shares’ significantly correlated with the number of donations (r=0.405,p=0.008)(r=0.515,p